Evaluation of the Environment in Operating Theater and Delivery Unit and Neonatal Care Unit at Al-Zahra Hospital for Women and Children - Maha. M. Alwan; Muthanna A. Al-Mahdawi (Academic Science Journal)
The study aimed to assess the efficiency of the sterilization process and the process of controlling contamination within the environment in AL- Zahra Hospital for women and children in AL- Muqdadiya located at Diyala province- Iraq, which extends at latitudes (-3.33 and -36.6) north and longitudes (-44.22 and 45.56) east, during the period from 25 December 2021 to 19 February 2022 due to deficiency of studies that are interested in this field. One hundred ninety - two of air sample was taken distributed to the hospital halls such as the surgical hall and its corridor that leads to it, the delivery hall and its corridor that leads to it, the sterile preterm unit and its corridor leds to it, the main hall of the units, and the air outside the hospital environment, where the samples were divided into two groups, the first one includes 96 samples collected in the morning before the beginning of work at 8 :00am and the second include 96 samples collected during the work at peak time 12:00 noon. The result was expressed by colony forming unit (CFU/m3). Bacterial microbial loads in hospital air ranged between 2-131 CFU/m3. Air bacterial loads in surgical hall ranged between 5-40, in a range 19.04 CFU/m3 and in the delivery hall ranged between 19-55.5, in a range 35.8 CFU/m3 and in the preterm infant hall 23.5-41.5, in a range30.5 CFU/m3 and in the main hall ranged between 34.5-89, in a range 60.4 CFU/m3 and in the outside air environment ranged between 39.5-115.5, in a range75.6 CFU/m3.